STUDY OF PARTICLE SIZE AND COMPACTION EFFECT ON COAL SPONTANEOUS COMBUSTION XYZA INC. JAMBI PROVINCE WITH ADIABATIC HEATING LABORATORY SCALE - Adita Sari, Nindya
Coal spontaneous combustion can be serious problem especially to mining company both in surface mining or underground mining. Guney, (1968) divided factors that affect coal spontaneous combustion into intrinsic factors and extrinsic factors. Intrinsic factors such as pyrite, moisture, particle size, etc. The extrinsic factors such as oxygen concentration, temperatur, and the other factors form the outside. This experiment is pointed to the effect of particle size (intrinsic factor) and degree of compaction (extrinsic factor) towards coal spontaneous combustion behavior. Particle size distribution that are used in this experiment are -10+14#, - 60+80# and -170+200# with the degree of compaction 0 kPa and 50 kPa. This particle size is chosen because the greater particle size above -10+14# has been experimented before (Syawaludin, 2016). The assumption for degree of compaction is based on ground pressure Bulldozer Komatsu D85ESS 50 kPa. In this experiment is used oxidation adiabatic heating method which is the oxygen gas with flow rate 0.05 L/minute is released in the experiment reactor. Besides, this study also conduct oxygen diffusion experiment to determine diffusion coefficient in every parameters. R70 value (Beamish, 2000) under condition 0 kPa from -10+14# to -170+200# are 21.053, 31.124, 68.789 for the degree of compaction 50 kPa are 36.000, 38.434, 46.723. Particle size and degree of compaction have great effect in order to undergo spontaneous combustion. The smaller coal particle size caused denser particle size so R70 become smaller and vice versa.